2010
DOI: 10.1111/j.1365-2486.2009.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of soil‐applied black carbon: downward migration, leaching and soil respiration

Abstract: Black carbon (BC) is an important pool of the global C cycle, because it cycles much more slowly than others and may even be managed for C sequestration. Using stable isotope techniques, we investigated the fate of BC applied to a savanna Oxisol in Colombia at rates of 0, 11.6, 23.2 and 116.1 t BC ha À1 , as well as its effect on non-BC soil organic C. During the rainy seasons of 2005 and 2006, soil respiration was measured using soda lime traps, particulate and dissolved organic C (POC and DOC) moving by satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
400
10
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 658 publications
(480 citation statements)
references
References 63 publications
32
400
10
8
Order By: Relevance
“…These findings are 564 consistent with previous studies that reported minimal DOC leaching from biochar-amended 565 field plots (Bell and Worrall, 2011;Major et al, 2010). Most of the DOC was lost during the first 566 flush, suggesting that the majority of leachable C may be removed during the first rain event 567…”
Section: Implications For C Sequestration 563supporting
confidence: 83%
“…These findings are 564 consistent with previous studies that reported minimal DOC leaching from biochar-amended 565 field plots (Bell and Worrall, 2011;Major et al, 2010). Most of the DOC was lost during the first 566 flush, suggesting that the majority of leachable C may be removed during the first rain event 567…”
Section: Implications For C Sequestration 563supporting
confidence: 83%
“…This figure compiles data from surface horizons of 20 long-term field experiments (up to 23 years) in temperate climate, using 13 C labelling to trace the residence time of bulk SOM and of individual molecular compounds. The variation in turnover time is also seen in the compounds of microbial origin analysed for 13 fire-derived carbon does undergo oxidation and transport, as we now know from archaeological settings 28 , soils 29,30 , and from breakdown products in river 31 and ocean water 32,33 . In a field experiment, firederived residues were even observed to decompose faster than the remaining bulk organic matter, with 25% lost over 100 years (ref.…”
Section: Soil Humic Substancesmentioning
confidence: 99%
“…Third, biochar has been applied as a soil additive and shown to produce multiple potential environmental and economic benefits. These include improved soil fertility and crop yield, carbon stabilization and storage, reduced emissions of greenhouse gases (specifically, N 2 O and CH 4 ) from soil, better retention and reduced leaching of nutrients (e.g., nitrogen and phosphorus), improved surface-and groundwater quality, and adsorption of organic and metallic contaminants [1,2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%